019 Evaluation of in-ear sensor systems for quantifying head impacts in youth football. (3rd March 2020) - Sandmo, Stian Bahr; McIntosh, Andrew S; Andersen, Thor Einar; Koerte, Inga K; Bahr, Roald
Abstract : Background: Wearable sensor systems have the potential to quantify head kinematic responses of head impacts in football. However, on-field use of sensors (e.g. accelerometers) remains challenging due to factors such as poor coupling to the head. Objective: To test the validity of a novel in-ear sensor for quantifying head-impact exposure in youth football. Design: Descriptive laboratory study/validation study. Setting: Youth football. Participants: Six male youth football players (15.3±0.3 years). Evaluations: In step 1, the sensor was mounted to a Hybrid III headform (HIII) and impacted with a linear impactor or football (range: 9–144 g). Accelerative forces, including peak linear acceleration (PLA), were obtained from both systems. In step 2, six youth soccer players wore sensors during a structured training protocol including heading and non-heading exercises; in step 3, they completed two regular football sessions. For each recorded accelerative event, PLA outputs were compared to video. Main outcome measurements: In step 1, random and systematic error were calculated using HIII as reference. In steps 2 and 3, mean values (±SD) were calculated for (1) all heading and (2) all non–heading events. Receiver operating characteristic curves were used to determine the sensor's discriminatory capacity in both on-field settings, and cut-off values for predicting outcomes were identified. Results: In step 1, random and systematic error were both 11% for PLA. In step 2, heading events resulted in higher absolute values (PLA=15.6±11.8 g) than non-heading events (PLA=4.6±1.2g); area under the curve (AUC) was 0.98. In step 3, AUC was >0.99. A 9 g cut-off value yielded a positive predictive value of 100% in the structured training protocol vs. 65% in regular football sessions. Conclusions: The in-ear sensor displayed considerable random error and overestimated head impact exposures substantially. It showed excellent on-field accuracy for discriminating headings from other accelerative events, but secondary means of verifying events are still necessary.